KINERJA PEGAWAI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KOTA PEKALONGAN - Indrawan Pramiyudha; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
According to government regulation no. 32 2004 concerning regional governance that the autonomy to the region intended to increase its efficiency and the efficiency of local government , the education office of youth and sports is one of government agencies has a high position as an element implementing in DINDIKPORA. DINDIKPORA have main task to take part of domestic affairs in education , youth and sports , and implement regional decentralization and deconcentration duty in education , youth and sports . The purpose of the research is to identify and analyze the performance, motivation and discipline against the performance of employees and to know the relationship between motivation and discipline with DINDIKPORA of Pekalongan. This research is using quantitative design research with respondents of the employees DINDIKPORA, The process begins with determine the samples from all employees DINDIKPORA of pekalongan .Using a questionnaire to obtained answers for each variable. The results of the study between the correlation of motivation and discipline of the performance of employees DINDIKPORA of pekalongan by using formulas Pearson Correlation there is a correlation between motivation and discipline with the performance of employees. According to the results of the correlation of Pearson, there is a significant correlation between motivation and discipline with the employee performance. The increase in the need to improve the employee performance.